Purification to apparent homogeneity and partial amino acid sequence of rat liver O6-alkylguanine-DNA-alkyltransferase. - Wilkinson, M C (1990)
O6-alkylguanine-DNA-alkyltransferase (ATase) activity was increased in rat liver from 80 to 320 fmoles/mg total protein 48 h after administration of 2-acetylaminofluorene at 60 mg/kg body weight. This tissue was used as a source of ATase which was purified by ammonium sulphate precipitation and DNA-cellulose, molecular exclusion and ion exchange chromatography (IEC). IEC purified material showed a major 24 kDa band after polyacrylamide gel electrophoresis (PAGE) with silver staining. Fluorography of purified ATase following incubation with [3H]-methylated substrate DNA and PAGE showed a single band at 24 kDa suggesting that, as with bacterial ATases, the protein itself accepts the alkyl group from O6-alkylguanine in substrate DNA during the repair reaction. Further purification of the protein using reverse phase HPLC resulted in a single peak representing approximately 125,000 fold purification. This was subjected to amino-terminal sequencing and it was found that the protein was blocked at the amino-terminal end: it was cleaved using trypsin or cyanogen bromide and the amino acid sequence of several reverse phase HPLC purified fragments was determined.